2009
DOI: 10.1074/jbc.m109.007625
|View full text |Cite
|
Sign up to set email alerts
|

The Isomerase Active Site of Cyclophilin A Is Critical for Hepatitis C Virus Replication

Abstract: Cyclosporine A and nonimmunosuppressive cyclophilin (Cyp) inhibitors such as Debio 025, NIM811, and SCY-635 block hepatitis C virus (HCV) replication in vitro. This effect was recently confirmed in HCV-infected patients where Debio 025 treatment dramatically decreased HCV viral load, suggesting that Cyps inhibitors represent a novel class of anti-HCV agents. However, it remains unclear how these compounds control HCV replication. Recent studies suggest that Cyps are important for HCV replication. However, a pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
222
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 178 publications
(231 citation statements)
references
References 47 publications
9
222
0
Order By: Relevance
“…Similarly, the host cellular protein CyPA is also known to be involved in the replication of these viruses 16, 34, 35. It has been reported that HCMV infection induces the generation of ROS minutes after entry into the host cell 4.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the host cellular protein CyPA is also known to be involved in the replication of these viruses 16, 34, 35. It has been reported that HCMV infection induces the generation of ROS minutes after entry into the host cell 4.…”
Section: Discussionmentioning
confidence: 99%
“…For HIV-1, the binding of CypA to the viral Capsid protein seems required (66), whereas the infection of E. coli by the filamentous phage fd is regulated by the Cyclophilin18-catalyzed cis/trans-isomer-ization of its Pro 213 (67,68). Regarding HCV and its mandatory host factor CypA, this important question remains to be answered (69). However, because mutations in the active site of CypA abolishing its PPIase activity also interfere with its binding property (69,70), it is challenging to distinguish between these two possible mechanisms, which are moreover not mutually exclusive.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding HCV and its mandatory host factor CypA, this important question remains to be answered (69). However, because mutations in the active site of CypA abolishing its PPIase activity also interfere with its binding property (69,70), it is challenging to distinguish between these two possible mechanisms, which are moreover not mutually exclusive. We show that CypA-catalyzed cis/trans (c 7 T) isomerization of Pro 314 is significantly faster when the structural motif is absent (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…At the present time, NIM811 and two other cyclophilin inhibitors are in clinical trials as co-treatments for hepatitis C virus (HCV). These compounds are thought to partially inhibit HCV replication by binding to cyclophilin A and possibly other cyclophilins, of which there are at least 16 expressed in mammalian cells [115][116][117]. Additional studies suggest that co-treatment with cyclophilin inhibitors and protease or polymerase inhibitors leads to a reduction in HCV replication and limits development of resistance to monotherapy alone [117][118][119][120].…”
Section: Targeting the Mptp In Acute Scimentioning
confidence: 99%